Activation Plan of the Cooperative in Cambodia - 김연수; 이상엽 (한국비교정부학보, 21(4), 2017)
Cambodia has very good potential for agriculture such as climate, land, and precipitation, etc. Nevertheless, owing to backward agricultural production technology and poor capacity of farmers, agricultural productivity of Cambodia is very poor compared with neighboring countries. Recently, to improve agricultural productivity, the Cambodian government enacted the Agricultural Cooperative Law and has made efforts to improve cultivation technology, treatment after harvest, and distribution environment of agricultural products. To achieve the goal, it also hope assistance from international development cooperation. Cambodian agricultural producers are placed in external diseconomy effects caused by unstable agricultural competitive market. This study intends to suggest an idea to remedy imbalance of agricultural production incomes by activating cooperatives. This study suggests the followings as ideas to activate cooperatives in Cambodia. First, considering that, because of poor infrastructure for improvement of agricultural productivity, activation of functions and operation of cooperatives should be promoted. Second, It is necessary to cultivate specialists for international cooperation to activate cooperatives. Third, by encouraging agricultural producers who lack agricultural productivity infrastructure to participate in operation of cooperatives, we need to create a new system to overcome the problem of the infrastructure. KCI Citation Count: 3